Aplikasi Sinar Ultraviolet C terhadap Pertumbuhan Koloni Candida albicans - Tira H. Skripsa; Gunawan Wibisono; Diah A. Purbaningrum; Yoghi B. Prabowo; Rizky M. Boedi (e-GiGi, 2026)
Abstract: Healthcare-associated infections (HAIs) often involve Candida albicans as the dominant pathogen. Various sterilization and disinfection procedures using autoclaves, chlorhexidine gluconate, alcohol, and ultraviolet exposure can be employed to reduce the risk. This study aimed to evaluate the effectiveness of Ultraviolet C (UV-C, 254 nm) in reducing the number of C. albicans colonies. This was an experimental laboratory study using a pre- and post-test control group design. A total of 120 Petri dishes containing C. albicans cultures were divided into three groups (one control and two treatment groups with varying durations of UV-C exposure). Colony reduction was calculated manually by comparing the control group with the treatment groups. Analysis was conducted on 1×10⁴ CFU/mL and 1×105 CFU/mL suspensions. The results of the One-Way ANOVA showed a significant difference in the reduction of C. albicans colonies among the treatment groups. The longer the UV-C exposure duration, the greater the observed colony reduction. These findings reinforce the effectiveness of UV-C (254 nm) in reducing the viability of C. albicans with a duration-dependent response pattern. In conclusion, exposure to UV-C light (254 nm) is proven effective in reducing the number of Candida albicans colonies. The longer the duration of exposure, the greater the reduction in the colony count. Keywords: Candida albicans; ultraviolet C   Abstrak: Infeksi terkait pelayanan kesehatan (HAIs) kerap melibatkan Candida albicans sebagai patogen dominan. Terdapat berbagai prosedur sterilisasi dan disinfeksi menggunakan autoklaf, klorheksidin glukonat, alkohol, dan paparan ultraviolet untuk menekan risiko tersebut. Penelitian ini bertujuan untuk mengevaluasi kemampuan sinar ultraviolet spektrum C (UV-C, 254 nm) menurunkan jumlah koloni C. albicans. Jenis penelitian ialah eksperimental laboratorik dengan rancangan pre- and post-test control group. Sebanyak 120 cawan Petri berisi biakan C. albicans dibagi menjadi tiga kelompok (satu kontrol dan dua perlakuan dengan variasi durasi paparan UV-C). Penurunan jumlah koloni dihitung secara manual dengan membandingkan kelompok kontrol dan kelompok perlakuan. Analisis dilakukan pada suspensi 1×10⁴ CFU/mL dan 1×105 CFU/mL. Hasil One-Way ANOVA menunjukkan perbedaan penurunan jumlah koloni C. albicans yang bermakna antar kelompok perlakuan. Semakin lama durasi paparan UV-C, semakin besar reduksi koloni yang diamati. Temuan ini menguatkan efektivitas UV-C (254 nm) dalam menurunkan viabilitas C. albicans dengan pola respons bergantung durasi paparan. Simpulan penelitian ini ialah paparan sinar UV-C (254 nm) terbukti efektif menurunkan jumlah koloni Candida albicans. Semakin lama durasi paparan, semakin banyak jumlah koloni yang berkurang. Kata kunci: Candida albicans; ultraviolet C (UV-C); healthcare-associated infections